Protein Kinase A in Human Retina: Differential Localization of Cβ, Cα, RIIα, and RIIβ in Photoreceptors Highlights Non-redundancy of Protein Kinase A Subunits - Roa, Jinae N.; Ma, Yuliang; Mikulski, Zbigniew; Xu, Qianlan; Ilouz, Ronit; Taylor, Susan S.; Skowronska-Krawczyk, Dorota (Frontiers in Molecular Neuroscience, 2021)
Protein kinase A (PKA) signaling is essential for numerous processes but the subcellular localization of specific PKA regulatory (R) and catalytic (C) subunits has yet to be explored comprehensively. Additionally, the localization of the Cβ subunit has never been spatially mapped in any tissue even though ∼50% of PKA signaling in neuronal tissues is thought to be mediated by Cβ. Here we used human retina with its highly specialized neurons as a window into PKA signaling in the brain and characterized localization of PKA Cα, Cβ, RIIα, and RIIβ subunits. We found that each subunit presented a distinct localization pattern. Cα and Cβ were localized in all cell layers (photoreceptors, interneurons, retinal ganglion cells), while RIIα and RIIβ were selectively enriched in photoreceptor cells where both showed distinct patterns of co-localization with Cα but not Cβ. Only Cα was observed in photoreceptor outer segments and at the base of the connecting cilium. Cβ in turn, was highly enriched in mitochondria and was especially prominent in the ellipsoid of cone cells. Further investigation of Cβ using RNA BaseScope technology showed that two Cβ splice variants (Cβ4 and Cβ4ab) likely code for the mitochondrial Cβ proteins. Overall, our data indicates that PKA Cα, Cβ, RIIα, and RIIβ subunits are differentially localized and are likely functionally non-redundant in the human retina. Furthermore, Cβ is potentially important for mitochondrial-associated neurodegenerative diseases previously linked to PKA dysfunction.